Buat Brand Produk dan Ajarkan Digital Marketing pada Usaha Kue Kering Khas Banyuwangi - Agus Supriono; Elma Oktavian; Cindera Rosa Damascena; Ebban Bagus Kuntadi; Suwali Suwali; Rizky Yanuarti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Banyuwangi City is a tourism icon, known for its local delicacies and souvenirs. Many tourists visit the city for its attractions and often seek items to take home as gifts. One of the local businesses specializing in selling traditional cookies is located in the Penganjuran subdistrict. However, this business has been significantly affected by the ongoing COVID-19 pandemic. The pandemic has caused a decline in economic activity, with many businesses experiencing reduced income or even closure. To address this issue, a community service program was initiated to help revive the local cookie business. The program aims to provide valuable knowledge and skills to the community during its implementation and beyond. Ultimately, the goal is to enable business owners to grow their operations and improve their marketing strategies.